Heavy Metal Levels in Adolescent and Maternal Blood: Association with Risk of Hypospadias. (4th March 2014) - Sharma, Tusha; Banerjee, Basu Dev; Yadav, Chandra Shekhar; Gupta, Piyush; Sharma, Sunil
Abstract : Background . Hypospadias is a part of testicular digenesis syndrome (TDS) which includes infertility, cryptorchidism, and spermatogenesis. Heavy metals act as endocrine disrupting compounds. Heavy metals such as cadmium, chromium, arsenic, and lead have been associated with male infertility, cryptorchidism, spermatogenesis, cancer, reproductive disorder, and neurological disorder. However, it remains an important issue to corroborate or refute the hypothesis that the role of heavy metals in male reproductive tract disorders. Hence, the present study was designed to investigate the possible association of heavy metal and risk of hypospadias by estimating the blood heavy metal levels. Methods . In this case control study, 50 hypospadias boys diagnosed and confirmed by a pediatric urologist and 50 randomly selected age-matched (1–5 years) healthy control boys not suffering from any clinically detectible illness and their mothers have been included and heavy metal levels in the blood of these subjects have been estimated by Atomic Absorption Spectrophotometer (AAS). Result . Significantly high levels of cadmium and lead have been observed in hypospadias cases; however, all heavy metal levels were present in higher concentration. Conclusion . Higher blood levels of cadmium and lead may be associated with the increased risk of hypospadias.